PELATIHAN PEMBUATAN KERIPIK REBUNG DI DESA BIREM RAYEUK KABUPATEN ACEH TIMUR - Desy Irafadillah Effendi; Nurmasyitah; Seprianto (Global Science Society, 2020)
Birem Rayeuk Village, East Aceh Regency is an area that is overgrown with bamboo tree. Bamboo shoots have long been known to the public as food ingredients. Bamboo shoots are usually processed into vegetables or other foods. Besides the delicious taste, bamboo shoots are rich in fiber and nutrients. Bamboo shoots contain protein, carbohydrates, fats, and vitamins. Even so, there are many people don’t know and there are still few who consume it. Therefore, in this community service activity, the service team conducted trained in making bamboo shoots chips which became one of the economically valuable snack innovations. The training method starts from preparing the meeting place, the community receives direction, socializes community service activities implementation plan, and ended with training in making bamboo shoots chips. The results of this community service are products of bamboo shoots chips that have a savory and delicious taste. In addition, bamboo shoots chips can be used as one of the business prospects that can be done with small capital and large profits.